2015
DOI: 10.1021/acs.iecr.5b01175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steam on the Reactivity of MgO-Based Sorbents in Precombustion CO2 Capture Processes

Abstract: Low-cost MgO-based sorbents were prepared through modification of natural dolomite and were found to be capable of capturing CO 2 from coal gas at elevated temperatures and pressures (i.e., 330°< T < 450 °C and P > 20 bar). The effect of steam on the reactivity of the MgO sorbents was investigated experimentally. The results indicate that the presence of steam significantly improves the overall rate of the carbonation reaction through two different mechanisms. The presence of steam improves the intrinsic rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Therefore, the primary focus of previous research efforts has been the development of approaches to reduce the limitations due to product layer formation. For example, Zarghami et al 16 found that increasing the system pressure to 20 bar and adding 30 vol. % water vapor improved the apparent rate of carbonation, leading in turn to an almost complete conversion of the solid sorbent.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the primary focus of previous research efforts has been the development of approaches to reduce the limitations due to product layer formation. For example, Zarghami et al 16 found that increasing the system pressure to 20 bar and adding 30 vol. % water vapor improved the apparent rate of carbonation, leading in turn to an almost complete conversion of the solid sorbent.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the pressure may increase the reaction rate, but this is problematic for practical applications [21]. Alternatively, the use of steam can improve the CO 2 sorption rates of MgO due to the formation of Mg(OH) 2 , [22]. Nevertheless, the practical temperature range for this sorbent is limited to 200-315 °C.…”
Section: Introductionmentioning
confidence: 99%
“…That the carbonation reaction of MgO is limited to its surface has been substantiated experimentally by the strong correlation between CO2 uptake and surface area [140]. It is possible to improve the CO2 uptake of MgO by fabricating materials with a high surface area of up to 1000 m 2 g -1 , achieving capacities of 20 wt% at temperatures between 25 -400 °C [59], [127]- [129], [140]- [142]. In Section 5.1, we describe how infrared spectroscopy has been used to gain further insight to how CO2 is adsorbed on the surface of pure MgO.…”
Section: Mgo-mgco3 Systemmentioning
confidence: 96%
“…In pre-combustion CO2 capture, e.g. for integrated gasification combined cycle (IGCC) power plants, partial pressures of CO2 from coal gas can range from 0.5 to 10 bar [59]- [61]. , respectively.…”
Section: Thermodynamic Properties Of Alkali Metal Oxide Sorbentsmentioning
confidence: 99%
See 1 more Smart Citation